Colonelism in the colony: the Old Republic in the Northwest of RS - Cremonese, Dejalma (2022)
This work aims to discuss coronelism, in the Brazilian political system, as a privileged mechanism for access and permanence in power. The main problem is what kind of relationship was established between partisan leaders and newly arrived colonists in the Northwest of RS? The hypothesis affirms that the relation was coronelista, marked by the control clientelista and authoritarian. The methodology used is qualitative, supported by bibliographical references, secondary research based on historical records and interviews about Rio Grande do Sul and especially the case of the municipality of Ijuí in the period between 1890-1930.